Novel Polymorphisms in the Myosin Light Chain Kinase Gene Confer Risk for Acute Lung Injury - Gao, Li; Grant, Audrey; Halder, Indrani; Brower, Roy; Sevransky, Jonathan; Maloney, James P; Moss, Marc; Shanholtz, Carl; Yates, Charles R; Meduri, Gianfranco Umberto; Shriver, Mark D; Ingersoll, Roxann; et al. (American journal of respiratory cell and molecular biology, 2006)
The genetic basis of acute lung injury (ALI) is poorly understood. The myosin light chain kinase (MYLK) gene encodes the nonmuscle myosin light chain kinase isoform, a multifunctional protein involved in the inflammatory response (apoptosis, vascular permeability, leukocyte diapedesis). To examine MYLK as a novel candidate gene in sepsis-associated ALI, we sequenced exons, exon-intron boundaries, and 2 kb of 5' UTR of the MYLK, which revealed 51 single-nucleotide polymorphisms (SNPs). Potential association of 28 MYLK SNPs with sepsis-associated ALI were evaluated in a case-control sample of 288 European American subjects (EAs) with sepsis alone, subjects with sepsis-associated ALI, or healthy control subjects, and a sample population of 158 African American subjects (AAs) with sepsis and ALI. Significant single locus associations in EAs were observed between four MYLK SNPs and the sepsis phenotype (P<0.001), with an additional SNP associated with the ALI phenotype (P=0.03). A significant association of a single SNP (identical to the SNP identified in EAs) was observed in AAs with sepsis (P=0.002) and with ALI (P=0.01). Three sepsis risk-conferring haplotypes in EAs were defined downstream of start codon of smooth muscle MYLK isoform, a region containing putative regulatory elements (P<0.001). In contrast, multiple haplotypic analyses revealed an ALI-specific, risk-conferring haplotype at 5' of the MYLK gene in both European and African Americans and an additional 3' region haplotype only in African Americans. These data strongly implicate MYLK genetic variants to confer increased risk of sepsis and sepsis-associated ALI.